2018
DOI: 10.1101/498055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functionally distinct high and low theta oscillations in the human hippocampus

Abstract: 22Based on rodent models, researchers have theorized that the hippocampus supports episodic 23 memory and navigation via the theta oscillation, a ∼4-10-Hz rhythm that coordinates brain-wide 24 neural activity. However, recordings from humans have indicated that hippocampal theta oscillations 25 are lower in frequency and less prevalent than in rodents, suggesting interspecies differences in 26 theta's function. To characterize human hippocampal theta, we examined the properties of theta 27 oscillations thro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 87 publications
(147 reference statements)
1
36
0
Order By: Relevance
“…We had previously shown that hippocampal theta power was indicative of movement onset in this task (Bush et al, 2017) and spatial memory retrieval in MEG (Kaplan et al, 2014). Other studies performing a different hybrid navigation and memory paradigm have suggested diverse roles for low theta depending on laterality and hippocampal subregion (Miller et al, 2018;Goyal et al, 2020;Herweg et al, 2020). There has been an increasing body of evidence to suggest that low frequency power decrease and high frequency power increase is associated with performance in a variety of tasks, with this "tilt" in the 1/frequency characteristic inherent to human EEG thought to reflect increased regional neural activity (Fellner et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…We had previously shown that hippocampal theta power was indicative of movement onset in this task (Bush et al, 2017) and spatial memory retrieval in MEG (Kaplan et al, 2014). Other studies performing a different hybrid navigation and memory paradigm have suggested diverse roles for low theta depending on laterality and hippocampal subregion (Miller et al, 2018;Goyal et al, 2020;Herweg et al, 2020). There has been an increasing body of evidence to suggest that low frequency power decrease and high frequency power increase is associated with performance in a variety of tasks, with this "tilt" in the 1/frequency characteristic inherent to human EEG thought to reflect increased regional neural activity (Fellner et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…The lesions in the Sharp and Koester (2008) study included both the MBs and supramammillary nuclei; however, our present findings would suggest that their results were at least in part driven by the loss of the MBs. Theta frequency is considered a mechanism for timing the flow of information in the hippocampus (Richard et al, 2013), and high-frequency theta in particular has been linked to spatial memory in both rodents and humans (Olvera-Cortés et al, 2002; Goyal et al, 2018). Furthermore, reducing the frequency of theta in otherwise normal animals impairs performance on spatial memory tasks (Pan and McNaughton, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The lesions in Sharp and Koester's study included both the mammillary bodies and supramammillary nuclei, however, our present findings would suggest their results were at least in part driven by the loss of the mammillary bodies. Theta frequency is considered a mechanism for timing the flow of information in the hippocampus (Richard et al, 2013) and high-frequency theta in particular has been linked to spatial memory in both rodents and humans (Goyal et al, 2018;Olvera-Cortes et al, 2002). Furthermore, reducing the frequency of theta in otherwise normal animals impairs performance on spatial memory tasks (Pan and McNaughton, 1997).…”
Section: Discussionmentioning
confidence: 99%